Mercado livre de energia no Ceará: concentração e poder de mercado - Travassos, Alexandre Barbosa (2019)
The present study evaluates if the adoption of the Free Market of Energy modality in Ceará brought more competition to the sector, making the energy market more competitive, and causing the price reduction. To analyze this question, the Herfindahl-Hirschman index (HHI) was used to measure the concentration and the Lerner index to measure market power, during the period from 2010 to 2018, where it was concluded that, in fact, there was a reduction of the concentration in the free energy market of Ceará, with the appearance of several companies that started to negotiate in the MLE-CE (Free Market of Energy of Ceará), without there is, however, market share of any of these companies, that could suggest the exercise of market power. It was also found that there was greater price stability in this market during the period studied.